Construction of Infectious Clones of Begomoviruses: Strategies, Techniques and Applications - Saad, Mohd Faiz Mat (Biology (Basel), 2021)
SIMPLE SUMMARY: Begomovirus has a wide host range and threatens a significant amount of economic damage to many important crops such as tomatoes, beans, cassava, squash and cotton. There are many efforts directed at controlling this disease including the use of insecticides to control the insect vector as well as screening the resistant varieties. The use of synthetic virus or infectious clones approaches has allowed plant virologists to characterize and exploit the genome virus at the molecular and biological levels. By exploiting the DNA of the virus using the infectious clones strategy, the viral genome can be manipulated at specific regions to study functional genes for host–virus interactions. Thus, this review will provide an overview of the strategy to construct infectious clones of Begomovirus. The significance of established infectious clones in Begomovirus study will also be discussed. ABSTRACT: Begomovirus has become a potential threat to the agriculture sector. It causes significant losses to several economically important crops. Given this considerable loss, the development of tools to study viral genomes and function is needed. Infectious clones approaches and applications have allowed the direct exploitation of virus genomes. Infectious clones of DNA viruses are the critical instrument for functional characterization of the notable and newly discovered virus. Understanding of structure and composition of viruses has contributed to the evolution of molecular plant pathology. Therefore, this review provides extensive guidelines on the strategy to construct infectious clones of Begomovirus. Also, this technique’s impacts and benefits in controlling and understanding the Begomovirus infection will be discussed.